Progress in Gene Editing Tools and Their Potential for Correcting Mutations Underlying Hearing and Vision Loss - Botto, Catherine; Dalkara, Deniz; El-Amraoui, Aziz (Frontiers in Genome Editing, 2021)
Blindness and deafness are the most frequent sensory disorders in humans. Whatever their cause — genetic, environmental, or due to toxic agents, or aging — the deterioration of these senses is often linked to irreversible damage to the light-sensing photoreceptor cells (blindness) and/or the mechanosensitive hair cells (deafness). Efforts are increasingly focused on preventing disease progression by correcting or replacing the blindness and deafness-causal pathogenic alleles. In recent years, gene replacement therapies for rare monogenic disorders of the retina have given positive results, leading to the marketing of the first gene therapy product for a form of childhood hereditary blindness. Promising results, with a partial restoration of auditory function, have also been reported in preclinical models of human deafness. Silencing approaches, including antisense oligonucleotides, adeno-associated virus (AAV)–mediated microRNA delivery, and genome-editing approaches have also been applied to various genetic forms of blindness and deafness The discovery of new DNA- and RNA-based CRISPR/Cas nucleases, and the new generations of base, prime, and RNA editors offers new possibilities for directly repairing point mutations and therapeutically restoring gene function. Thanks to easy access and immune-privilege status of self-contained compartments, the eye and the ear continue to be at the forefront of developing therapies for genetic diseases. Here, we review the ongoing applications and achievements of this new class of emerging therapeutics in the sensory organs of vision and hearing, highlighting the challenges ahead and the solutions to be overcome for their successful therapeutic application in vivo.